Locoregional therapies in cholangiocarcinoma. (October 2017) - Labib, Peter L; Davidson, Brian R; Sharma, Ricky A; Pereira, Stephen P
Cholangiocarcinoma is a rare and aggressive malignancy of the biliary tract. Complete surgical resection can be curative, but the majority of patients are diagnosed with advanced disease and usually die within a year of diagnosis. Most deaths are attributable to local disease progression rather than distant metastases, supporting the use of locoregional therapies. There is evidence that locoregional therapies can provide local tumor control resulting in increased survival while avoiding some of the side effects of systemic treatments, increasing potential treatment options for patients who may be unsuitable for systemic palliative treatments. This review considers the evidence for locoregional therapies in cholangiocarcinoma, which can be classified into endoscopic, vascular, percutaneous and radiation oncological therapies. Current guidelines do not recommend the routine use of locoregional therapies due to a lack of prospective data, but the results of ongoing trials are likely to increase the evidence base and impact on clinical practice.